E-СOMMERCE IN RUSSIA: STATUS AND PROSPECTS - V. K. Shaidullina (Вестник университета, 2019)
Features and prospects of the Russian market of retail electronic trade in physical goods have been considered. It has been established, that over the next few years the following factors will affect the growth of online trade turnover: the development of cross-border exports; the convergence of offline and online trade; the expansion of the range of products (mainly through products and delivery of ready meals); deeper personalization of offers for the purchase of goods, combined with previously purchased things; the development of mobile retail.